A MODEL OF SYNERGY OF TOURISM DESTINATION DEVELOPMENT IN KARANGANYAR REGENCY - Bambang Mursito; Harini Harini; Eny Kustiyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The objective of research was to describe many attempts taken to develop tourism destination and to formulate a synergistic model in developing tourism destination in Karanganyar Regency. This study was a combination of descriptive qualitative and applied researches. Data collection was carried out through interviewing informants in-depth, data validity test using triangulation, and data analysis using interactive model. The result of research showed that the factors affecting a successful development of destination were: varying resources, destination’s accessibility, facility, comfort, and stakeholders’ participation. For that reason, synergies were required between destination organizers in policy making, between destination organizers and tourism office in the term of fund and institutional reinforcement, between organizer and surrounding people in the term of object maintenance and mutual benefit, between organizers and SME performers in providing service needed by visitors and souvenir, between organizer and empowerment institution, between organizer and local government as owner and mentor, and between organizers and high education through community service program. Synergy may include cooperation, governance policy, fund allocation, supervision, research, and training. Keywords: Synergy, Tourism Destination, Accessibility, Stakeholder